Seismic Performance Assessment of Optimal Tandem-Based Tuned Mass Damper Inerters - Maziar Fahimi Farzam; Shahram Ajori; Himan Hojat Jalali; Rim Najmeddine (Buildings)
In the current work, two novel tandem-based tuned mass damper configurations are introduced. These configurations extend the recently proposed tuned tandem mass damper inerter (TTMDI) by replacing the linking dashpot with an inerter (i.e., the inerter-connected TTMDI (ICTTMDI)), and an integrated tuned tandem mass damper inerter (I-TTMDI) by integrating recently proposed tuned tandem mass damper (TTMD) configurations. The control efficiency of the optimally designed dampers for a single-degree-of-freedom (SDOF) system was evaluated in a uniform framework to reveal and compare the performances of the ICTTMDI and I-TTMDI with those of other recently proposed tandem-based configurations. The optimum design of all the studied configurations was determined by the particle swarm optimization (PSO) algorithm. The evaluation of the performances included the effectiveness in the frequency domain and that of the norm and maximum reduction in the displacement and absolute acceleration in the time domain under 21 earthquake records with different characteristics. Additionally, the strokes of the dampers, the structure energies, and the power spectral densities (PSDs) of the responses were investigated. The optimum design of the I-TTMDI revealed the best configuration by determining the optimum distributions of the mass and inertance between the tandem mass and inerter links, respectively. The proposed configuration not only demonstrated improved response reduction across the displacement and acceleration measures but also maintained remarkable robustness under 21 earthquake records (far-fault, near-fault forward-directivity, and fling-step records). Furthermore, the advantages of the side inerter distribution were particularly effective at widening the operating frequency band, breaking through the traditional limitations of TMD-based devices. The consistent performances of the newly proposed configurations prove that they can be used to advance the development of more reliable structural control systems.